Hadis Gender: Meneguhkan Peran Perempuan di Ranah Publik - Apriliah, Apriliah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This article aims to describe gender hadith in the context of affirming the role of women in the public sphere. This research uses a qualitative approach through library research. The results of this study found that men and women have the same equality, in the fulfillment of their rights and obligations where there are equal conditions for men and women to have the opportunity to contribute and participate in the public sphere. This study presents three hadith related to the role of women in the political, educational and social spheres of society.